Implementation of Frugal Innovation Approach in Moroccan Industry through the Development of a New Frugal System - Bilal Karroumi; Abdelfettah Sedqui (Journal of Engineering)
To keep pace with economic growth in an environment marked by globalization, competition, and the significant magnitude of market requirements, companies must be dynamic to adapt quickly to new demands. This dynamism must be achieved through frugal projects aimed at achieving better performance with fewer resources. In line with this vision, we have proposed a new frugal innovation approach to develop a new concept of machines to meet the requirements of Smart Automation, which is the main element of the transformation plan defined by our company as a strategy for the coming years. This strategy aligns with the direction set by Morocco for the second generation of the Industrial Acceleration Plan 2021–2025. This work serves to introduce the objectives of the second-generation Industrial Acceleration Plan in Morocco, describe a company transformation strategy with an emphasis on the Smart Automation component and its context, explain frugal innovation applications within our organization and their outcomes, and outline the project and frugal innovation approach perspectives in Morocco. The results demonstrate the effectiveness of the newly proposed and implemented concept of frugal innovation, illustrated in a cost reduction of 59.7% compared with the manual process, of less than 56.3% compared with the existing semi-automatic process, and of less than 36.8% compared with the fully automatic process and in the improvement of quality by a reduction in customer complaints of 72.7% and in the scrap rate percentage of 0.2%. This has been achieved by providing cost-effective solutions in our competitive automotive environment. These results reinforce the importance of the approach in its global application.